Interruption and defaulting of multidrug therapy against leprosy: population-based study in Brazil's Savannah Region. - Jorg Heukelbach; Olga André Chichava; Alexcian Rodrigues de Oliveira; Kathrin Häfner; Friederike Walther; Carlos Henrique Morais de Alencar; Alberto Novaes Ramos; Adriana Cavalcante Ferreira; Liana Ariza (Public Library of Science (PLoS), 2011)
BACKGROUND: Low adherence to multidrug therapy against leprosy (MDT) is still an important obstacle of disease control, and may lead to remaining sources of infection, incomplete cure, irreversible complications, and multidrug resistance. METHODOLOGY/PRINCIPAL FINDING: We performed a population-based study in 78 municipalities in Tocantins State, central Brazil, and applied structured questionnaires on leprosy-affected individuals. We used two outcomes for assessment of risk factors: defaulting (not presenting to health care center for supervised treatment for >12 months); and interruption of MDT. In total, 28/936 (3.0%) patients defaulted, and 147/806 (18.2%) interrupted MDT. Defaulting was significantly associated with: low number of rooms per household (OR = 3.43; 0.98-9.69; p = 0.03); moving to another residence after diagnosis (OR = 2.90; 0.95-5.28; p = 0.04); and low family income (OR = 2.42; 1.02-5.63: p = 0.04). Interruption of treatment was associated with: low number of rooms per household (OR = 1.95; 0.98-3.70; p = 0.04); difficulty in swallowing MDT drugs (OR = 1.66; 1.03-2.63; p = 0.02); temporal non-availability of MDT at the health center (OR = 1.67; 1.11-2.46; p = 0.01); and moving to another residence (OR = 1.58; 95% confidence interval: 1.03-2.40; p = 0.03). Logistic regression identified temporal non-availability of MDT as an independent risk factor for treatment interruption (adjusted OR = 1.56; 1.05-2.33; p = 0.03), and residence size as a protective factor (adjusted OR = 0.89 per additional number of rooms; 0.80-0.99; p = 0.03). Residence size was also independently associated with defaulting (adjusted OR = 0.67; 0.52-0.88; p = 0.003). CONCLUSIONS: Defaulting and interruption of MDT are associated with some poverty-related variables such as family income, household size, and migration. Intermittent problems of drug supply need to be resolved, mainly on the municipality level. MDT producers should consider oral drug formulations that may be more easily accepted by patients. Thus, an integrated approach is needed for further improving control, focusing on vulnerable population groups and the local health system.